2006
DOI: 10.1523/jneurosci.4545-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit Interactions in EAAT4 Glutamate Transporters

Abstract: Excitatory amino acid transporters (EAATs) play a central role in the termination of synaptic transmission and in extracellular glutamate homeostasis in the mammalian CNS. A functional transporter is assembled as oligomer consisting of three subunits, each of which appears to transport glutamate independently from the neighboring subunits. EAATs do not only sustain a secondary-active glutamate transport but also function as anion channel. We here address the question whether intersubunit interactions play a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 34 publications
(75 reference statements)
5
39
2
Order By: Relevance
“…EAAT4 has one of the highest chloride permeabilities among all the glutamate transporter subtypes (Fairman et al, 1995), and a recent study has suggested that the individual subunits of EAAT4 interact cooperatively in gating glutamate-activated anion currents (Torres-Salazar and Fahlke, 2006). We therefore measured FLIC in EAAT4 to determine whether or not its subunits interact cooperatively in gating the anion conductance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EAAT4 has one of the highest chloride permeabilities among all the glutamate transporter subtypes (Fairman et al, 1995), and a recent study has suggested that the individual subunits of EAAT4 interact cooperatively in gating glutamate-activated anion currents (Torres-Salazar and Fahlke, 2006). We therefore measured FLIC in EAAT4 to determine whether or not its subunits interact cooperatively in gating the anion conductance.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a recent study suggested that the individual subunits of EAAT4 function cooperatively in gating the anion conductance. The authors reported a sigmoidal concentration dependence for glutamate with Hill coefficients Ն3 and suggested that multiple glutamate binding sites must be occupied to activate the anion conductance (Torres-Salazar and Fahlke, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiology-For expression in oocytes, cRNA was synthesized from MluI-linearized pTLN2-hEAAT3 (24) or from NheI-linearized pGEMHE-R501C rEAAT4 (20) templates through use of MESSAGE machine kits (Ambion, Austin, TX). Injection and handling of oocytes were performed as described elsewhere (25).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast R501C rEAAT4, like WT rEAAT4, is inactivated by positive voltages (Fig. 2B) (8,20,25), resulting in decreased channel open probabilities and time-dependent current amplitude reductions (arrow) (8,25,34). WT hEAAT3 currents are greatly increased in the presence of extracellular glutamate, but are not responsive to serine (Fig.…”
Section: Eaat3 and Eaat4 Form Hetero-oligomeric Transporters-mentioning
confidence: 98%
See 1 more Smart Citation